A=(2x+7)(2x-3)

Simple and best practice solution for A=(2x+7)(2x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for A=(2x+7)(2x-3) equation:



=(2A+7)(2A-3)
We move all terms to the left:
-((2A+7)(2A-3))=0
We multiply parentheses ..
-((+4A^2-6A+14A-21))=0
We calculate terms in parentheses: -((+4A^2-6A+14A-21)), so:
(+4A^2-6A+14A-21)
We get rid of parentheses
4A^2-6A+14A-21
We add all the numbers together, and all the variables
4A^2+8A-21
Back to the equation:
-(4A^2+8A-21)
We get rid of parentheses
-4A^2-8A+21=0
a = -4; b = -8; c = +21;
Δ = b2-4ac
Δ = -82-4·(-4)·21
Δ = 400
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$A_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$A_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{400}=20$
$A_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-8)-20}{2*-4}=\frac{-12}{-8} =1+1/2 $
$A_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-8)+20}{2*-4}=\frac{28}{-8} =-3+1/2 $

See similar equations:

| 5(1x-3)=2x+6 | | 37-u=293 | | 3−-g=5 | | 10-3f=7 | | -25y-25=-75+75 | | 3(2x+5)=-5(3x-5) | | 7=7r | | c/2+-8=-10 | | 13-8*3=x | | 3a+1=5a+2 | | 12x-40=10x-22 | | 2=3y | | w=0.9/100 | | a-1-8=-9 | | 1/2(x^2-36)=8 | | -n+8n=14 | | (=-8x-7) | | 12=8x+20 | | 6x-3+9x=7x+4-9x | | u/6-2.5=-21.7 | | c/4+14=16 | | -25y+75=-75-25 | | 4(-8x-7=) | | .6x+5=20-x | | c/4+ 14= 16 | | y-34=209 | | 6m+6=2m-10 | | (4x^2+5x)/3=67500 | | 2+-z=-2 | | 4=d+12 | | -12=15r | | 4(x+4)-3(x+1)=-4 |

Equations solver categories